"Design and Synthesis of 3D‐Ordered Mesoporous Co3O4 Nanostructures for Their Improved Supercapacitance and Photocatalytic Activity". Issue 30 (23rd October 2017) - Sheikh, Mehraj U. D.; Pandit, Umar J.; Naikoo, Gowhar A.; Thomas, Molly; Bano, Mustri; Ahirwar, Devendra; Khan, Farid
Abstract: We synthesized Co3 O4 and Co3 O4 @Au‐NPs nano structures via simple and economical strategy for high‐performance supercapacitors. Co3 O4 @Au‐NPs modified glassy carbon electrode exhibited excellent electrochemical performance including high specific capacitance of 683 Fg −1 (current density of 0.5 Ag −1 ), better retention capability of 65% at high current density (10 Ag −1 ) with remarkable cycling stability in 1000 continuous cycles at 0.5 Ag −1 current density (only 6% loss after 1000 cycles) and high energy and power densities (94.86 Whkg − 1 and 3.48 kWkg −1 ). The photocatalytic activity of the synthesized mesoporous structures against Methylene Blue dye was also carried out and compared with the standard P25. The study showed that the presence of gold nanoparticles has increased the photocatalytic activity of synthesized porous Co3 O4 to many folds. From the results it is believed that the addition of gold nanoparticles (Au‐NPs) has largely increased the supercapacitor and photocatalytic activity of Co3 O4 . Abstract : Mesoporous Co3 O4 @Au‐NPs showing high energy and power densities (94.86 Whkg − 1 and 3.48 k Wkg −1 ) respectively and degradation power of 98% against Methylene Blue dye.